Thousands of bats: A portrait of the chiropteran fauna of Palmas city, Central Brazil - Benvindo-Souza, Marcelino; Souza Santos, Lia Raquel de; Elias Borges, Rinneu; Alves de Assis, Rhayane [UNESP]; Silva, Daniela De Melo E.; Zortea, Marlon; Missel Pacheco, Susi (Wiley-Blackwell, 2021)
Urban development remodels the natural landscape and reconfigures local faunal communities. This study investigated for the first time the composition of bats in the city of Palmas, a rapidly growing urban centre in the state of Tocantins, Brazil. We recorded twenty-three species of bats, most of them frugivorous, and we try to launch light on a large colony of urban insectivorous bats. This bat colony contained an estimated one million broad-eared bats (Nyctinomops laticaudatus), and resided under the Fernando Henrique Cardoso Bridge of Friendship and National Integration, over the Tocantins River, between April and the beginning of October. This site has been certified as a Site of Special Importance for Bat Conservation by the Latin American and Caribbean Bat Conservation Network. The protection of the city's bats in general, and the bridge colony, in particular, will depend on efforts to raise the awareness of state and municipal authorities, programmes of environmental education and even the exploitation of the potential for local tourism.
Keywords: bridge; chiropterans; conservation; urban fauna; urbaniszation